THE INFLUENCE OF CORPORATE GOVERNANCE AND AUDIT QUALITY ON TRUSTED FINANCIAL STATEMENTS THROUGH FINANCIAL DISTRESS IN BUMN HOLDINGS IN INDONESIA - Indra Setiawan,; Tri Widyastuti,; Derriawan, Derriawan; Amilin, Amilin; Zulkifli, Zulkifli (International Journal of Social Science, 2023)
This study aims to analyze the effect of corporate governance and audit quality on trusted financial reports through financial distress. The analytical tool used in this study is the Structual Equation Model (SEM) with Partial Least Square (PLS), while the sample used in this study is 68 BUMN Holding business units in Indonesia. The research respondents were auditors who had experience in auditing BUMN Holdings. The results of the study show that corporate governance has a positive effect in encouraging the creation of trusted financial reports. Corporate governance has no significant effect in encouraging the creation of BUMN Holding financial distress in Indonesia. Audit quality has a positive effect in encouraging the creation of trusted financial reports. Audit quality has a positive effect on financial distress. Financial distress has a negative effect on trusted financial reports. This research provides insight into the field of financial risk management research. The insignificant relationship between corporate governance and financial distress is an important finding, because most previous studies have concluded that corporate governance variables have a direct effect on financial distress, both positive and negative. Given the complexity of the relationship between corporate governance and financial distress, more in-depth further research can be conducted to explain in more detail why this relationship is not significant. Qualitative approaches such as case studies, interviews or comparative analysis can be used to gain deeper insight into the context and mechanisms underlying these findings